Evaluation of refractive correction for standard automated perimetry in eyes wearing multifocal contact lenses - Kazunori Hirasawa; Hikaru Ito; Yukari Ohori; Yui Takano; Nobuyuki Shoji (International Journal of Ophthalmology, 2017)
AIM: To evaluate the refractive correction for standard automated perimetry (SAP) in eyes with refractive multifocal contact lenses (CL) in healthy young participants. METHODS: Twenty-nine eyes of 29 participants were included. Accommodation was paralyzed in all participants with 1% cyclopentolate hydrochloride. SAP was performed using the Humphrey SITA-standard 24-2 and 10-2 protocol under three refractive conditions: monofocal CL corrected for near distance (baseline); multifocal CL corrected for distance (mCL-D); and mCL-D corrected for near vision using a spectacle lens (mCL-N). Primary outcome measures were the foveal threshold, mean deviation (MD), and pattern standard deviation (PSD). RESULTS: The foveal threshold of mCL-N with both the 24-2 and 10-2 protocols significantly decreased by 2.2-2.5 dB CONCLUSION: Despite the induced mydriasis and the optical design of the multifocal lens used in this study, our results indicated that, when the dome-shaped visual field test is performed with eyes with large pupils and wearing refractive multifocal CLs, distance correction without additional near correction is to be recommended.